THE ANALYSIS OF THE WORK LOAD EFFECT AND MOTIVATION ON EMPLOYEES PERFORMANCE WITH EMPLOYEE TRAINING AS INTERVENING VARIABLES - Wardoyo, Wardoyo (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to examine and analyze the effect of workload and motivation on employee performance with training as an intervening variable case study at the Head Office of the Directorate General of Railways. This research was conducted at the Head Office of the Directorate General of Railways. The type of approach used is quantitative description with explanatory research. The research sample of 155 respondents with the sampling technique used was stratified proportional random sampling. In this research, data analysis uses validity test, reliability test, T test, and path analysis. From the results of the T test shows that there is an effect of workload on employee performance, there is an effect of motivation on employee performance, there is an influence of workload on training, there is an effect of motivation on training, and there is the influence of training on employee performance. From the results of path analysis (path analysis) shows that the effect of workload on employee performance with training as an intervening variable has no significant effect, which means there is no mediating effect. the effect of Employee Motivation on employee performance with training as an intervening variable has a significant effect, which means there is an influence of mediation.